Identification of the species of reservoirs and hosts of the rabies virus and other pathogens by sequencing of the cytochrome-b mitochondrial DNA gene - Carnieli Jr., P.; Batista, H. B.C.R.; Schereffer, K. C.; Fahl, W. O.; Lima, J. Y.O.; Oliveira, R. N.; Castilho, J. G.; Iamamoto, K.; Carrieri, M. L.; Kotait, I. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The identification of animal species that transmit pathogens such as the rabies virus is of the utmost importance for public health and the natural history of infectious and contagious diseases. Diagnostic laboratories very often receive mauled or decomposing animal carcasses, particularly of bats, rendering morphometric identification unviable. The existence of different regional names for the same animal, morphological variability and the lack of staff trained in zoological identification constitute a serious problem for epidemiological surveillance. Molecular techniques are used routinely and effectively in systematics, evolution and ecology to identify species and can even be used to identify hybrids that originated from genetically close animals, in which the differences very often go undetected by morphometry. Some mitochondrial DNA (mt- DNA) genetic markers, such as control region sequences and the genes encoding cytochromes b and c, are frequently used in the genetic identification of species. Many of the genetic sequences for these genes are stored in public-domain websites such as GenBank, allowing new sequences to be compared with existing ones in databases. The objective of this study is to build a database with genetic sequences from the cytochrome b gene of rabies reservoir species for use in the identification of these species. mt-DNA fragments were amplified and sequenced as described previously by Carnieli et al. (2008), using the primers 5’- CGACTAATGACATGAAAAATCACCGTTG-3’ (sense) and 5’- TATTCCCTTTGCCGGTTTACAAGACC-3’ (antisense) described by Martins et al. (2007). Sixty-six mt-DNA samples from different species of wingless Brazilian mammals and fifty-four samples from different species of chiropterans were sequenced. Analysis of the genetic sequences from these wingless mammals highlighted the problem of genetic identification of species as only a few sequences of mt-DNA from wingless mammals of Brazil were found in GenBank. For example, there are seven species of marmosets (genus Callithrix) but mt-DNA sequences for only some of them are deposited in GenBank. However, the cytochrome b gene sequences obtained from bats in this study, together with morphometric identification carried out in parallel, allowed us to name the species with certainty. From the fifty-four mt-DNA samples from chiropterans, nineteen species from eight genera and four different families were identified. Thus, the method described here is efficient in the identification of animal species and the search for samples of mt-DNA in Natural History Museums and Zoos may complement and certify unequivocally the sequences in the database under construction.